John Locke and Property as a Human Right Today: Towards a new Theory of Property Rights (Hekima Review, 2010)
Personal ownership as opposed to exclusive private ownership of property is the main subject of Enyeribe’s book. He is of the view that in the world of injustice and inequality where a few people own too much at the expense of others, universal personal ownership is a better alternative to exclusive private ownership. Enyeribe presents an account and powerful analysis of Locke’s teaching on private ownership.